The Relationship Between Parental Attachment and Cyberbullying with the Mediating Role of Social Media Dependency in Students - Shakeri, Sara; Homayouni, Alireza; Sadeghi, Jamal (Mental Health and Lifestyle Journal, 2026)
The present study aimed to examine the relationship between parental attachment and cyberbullying, considering the mediating role of social media dependency among students. The research employed a descriptive correlational design based on structural equation modeling. The statistical population consisted of all male upper secondary school students, from whom 280 participants were selected through convenience sampling. Participants completed the Parental Attachment Questionnaire developed by Armsden and Greenberg (1987), the Cyberbullying Questionnaire by Antoniadou et al. (2016), and the Social Media Dependency Scale developed by Usman and Shahnawaz (2020). Data were analyzed using structural equation modeling based on multivariate regression through SPSS version 18 and AMOS version 23 software. The results indicated a significant negative relationship between parental attachment and cyberbullying, as well as a significant positive relationship between social media dependency and cyberbullying. Furthermore, parental attachment exerted an indirect effect on cyberbullying through social media dependency. Model fit indices supported the adequacy of the proposed structural model, and 34% of the variance in the dependent variable was explained by the model variables. These findings confirm the important role of parent–child relationships and adolescents’ level of engagement in social media in preventing cyberbullying behaviors.